Potential Study of Panyaweuyan Terrace System in Indonesia To Be National Important Agricultural Heritage System: A Qualitative approach - Sulaksana, Jaka; Sudirno, Dadang; Wijaya, Acep Atma; Umyati, Sri (MAHATANI: Jurnal Agribisnis (Agribusiness and Agricultural Economics Journal), 2024)
The objectives of this activity are as follows: To accurately analyze the development potential of the Panyaweuyan terracing area as a national agricultural and food heritage (NIAHS); provide complete and integrated advice or recommendations in the development of the Panyaweuyan terracing area as a national agricultural and food heritage (NIAHS). The research location is the Panyaweuyan terracing area as a national agricultural and food heritage (NIAHS), namely in the Panyaweuyan Agrotourism Area, Argapura District, Majalengka Regency. The implementation time is August-September 2021. Agricultural activities carried out on Panyaweuyan terraced land can provide ecosystem services related to global warming and global climate change at least prevent erosion, through the terracing system. These ecosystem services are in the form of water resource management, conservation of agricultural diversity, low carbon society, zero waste agricultural systems, and renewable energy practices. The need for the development of a tourism promotion cooperation network, the need for the implementation of Panyaweuyan tourism promotion at home and abroad, the need for an increase in supporting infrastructure for tourist areas, the need for an increase in adequate road access to the Panyaweuyan area.